Optimisation Cesarean Section Rates Using Robson Ten Group Classification - Dr. Manali Kagathara; Dr Stuti Shah; Dr. Aayush Patel, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Cesarean section (CS) rates are increasing globally, leading to concerns about maternal and neonatal complications, rising healthcare costs, and adverse long-term reproductive outcomes. The Robson 10-Group Classification System (TGCS) is widely endorsed as a standard tool for auditing and comparing CS rates. Objective: To evaluate the impact of targeted interventions—guided by Robson Classification analysis—on reducing CS rates in a tertiary care hospital over a six-month period. Methods: A prospective pre-post interventional study was conducted over six months. In the pre-intervention phase (July–September 2024), CS rates were audited using the Robson Classification to identify high-contributing groups. Based on this analysis, three key interventions were implemented during the intervention phase (October–December 2024): 1. Enhanced Intrapartum Monitoring: Continuous evaluation of labor progression. 2. Bishop Score–Based Induction: Optimized induction decision-making to minimize unnecessary CS. 3. Antenatal Strategies: Aggressive management of genitourinary infections, increased antenatal care visits with targeted counseling on danger signs, and promotion of maternal exercises to prevent preterm labor. Data from 3,527 deliveries (all deliveries ≥24 weeks’ gestation) were compared between the two phases. Statistical significance was assessed using Chi-square tests and multivariate regression (p < 0.05 considered significant). Results: Pre-intervention, the overall CS rate was 45.42%. Post-intervention, the CS rate declined significantly to 37.54% (p < 0.05). The major contributors to CS were: - Robson Group 5: Women with previous CS (single cephalic, term pregnancies). - Robson Group 2: Nulliparous women with induced labor or prelabor CS. - Robson Group 10: Preterm pregnancies, which showed a significant reduction in CS rates following enhanced antenatal management. Additionally, an increase in the vaginal birth after cesarean (VBAC) rate was observed in Group 5 post-intervention. Conclusion: A structured audit using the Robson Classification combined with targeted intrapartum and antenatal interventions significantly reduced CS rates in our tertiary care hospital. These findings support the broader adoption of similar quality-improvement strategies to optimize maternal and neonatal outcomes.